Digestive systems of livestock [ a basic look - Bishara, Joseph N.; Cawthron, Scott; Grant, Ron , 1927-; Pond, K. R.; Creative Educational Video, Inc (Lubbock, TX : CEV Multimedia, 2000)
Explains the basic anatomy of livestock digestive systems: methods of prehension, different types of digestive systems and basic structures associated with the digestive tract
1. Prehension -- 2. Comparison of digestive tracts -- 3. Monogastrics and poultry -- 4. Ruminants
Instructor : Bo Brock
DVD
English
Keywords: Digestion; Veterinary physiology